Drug education in victorian schools (DEVS): the study protocol for a harm reduction focused school drug education trial - Midford Richard (BMC Public Health, 2012)
Abstract Background This study seeks to extend earlier Australian school drug education research by developing and measuring the effectiveness of a comprehensive, evidence-based, harm reduction focused school drug education program for junior secondary students aged 13 to 15 years. The intervention draws on the recent literature as to the common elements in effective school curriculum. It seeks to incorporate the social influence of parents through home activities. It also emphasises the use of appropriate pedagogy in the delivery of classroom lessons. Methods/Design A cluster randomised school drug education trial will be conducted with 1746 junior high school students in 21 Victorian secondary schools over a period of three years. Both the schools and students have actively consented to participate in the study. The education program comprises ten lessons in year eight (13-14 year olds) and eight in year nine (14-15 year olds) that address issues around the use of alcohol, tobacco, cannabis and other illicit drugs. Control students will receive the drug education normally provided in their schools. Students will be tested at baseline, at the end of each intervention year and also at the end of year ten. A self completion questionnaire will be used to collect information on knowledge, patterns and context of use, attitudes and harms experienced in relation to alcohol, tobacco, cannabis and other illicit drug use. Multi-level modelling will be the method of analysis because it can best accommodate hierarchically structured data. All analyses will be conducted on an Intent-to-Treat basis. In addition, focus groups will be conducted with teachers and students in five of the 14 intervention schools, subsequent to delivery of the year eight and nine programs. This will provide qualitative data about the effectiveness of the lessons and the relevance of the materials. Discussion The benefits of this drug education study derive both from the knowledge gained by trialling an optimum combination of innovative, harm reduction approaches with a large, student sample, and the resultant product. The research will provide better understanding of what benefits can be achieved by harm reduction education. It will also produce an intervention, dealing with both licit and illicit drug use that has been thoroughly evaluated in terms of its efficacy, and informed by teacher and student feedback. This makes available to schools a comprehensive drug education package with prevention characteristics and useability that are well understood. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12612000079842